Os sem religião: motivações e causas junto aos jovens do ensino médio das escolas públicas e privadas de Boa Vista - RR - Silva, Maria dos Santos de Jesus (2015)
This Dissertation has as objective to analyze the causes, the concept and to present the motivations to verify the number of the individuals declared without religion in Roraima, considering the result of the Census / IBGE, from 2000 to 2010. To turn viable this research, it was used a methodology that consists of the bibliographical research of Marià Corbí and several authors of the Brazilian religious field and in the research of field with the application of a mixed questionnaire of 10 subjects to a sample chosen of 756 students at the age group of 15 to 20 years, declared " without religion ", in the Public State Schools and the Peculiar ones of Boa Vista. In Roraima it is verified that the phenomenon of the "without religion" already occupies the third place in the classification of the religions in the State and that most of the declared "without religion" don't have entail with the Church, religious institution, but they believe in God. It is a group composed of several religious credos and, in small number, they identified the atheistic and agnostic individuals' presence. It is sensed, that the youths "without religion" of Roraima following the same characteristics of the without religion of the other Brazilian states. They are looking for the experience of a spirituality out of the religious institution, but not in the model without faith, without myth speculated in Mariá Corbí 2010, that it believes in a spirituality without religion, cultivated by the road of the silent knowledge.